2020
DOI: 10.1007/s11136-020-02537-y
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a conceptual model and patient-reported outcome measures for assessing symptoms and functioning in patients with heart failure

Abstract: Purpose Heart failure (HF) is a common condition that places considerable burden on patients. We aimed to develop a patient-reported outcome (PRO) measure to assess the symptoms and impacts of HF. Methods Phase 1: a targeted literature review, expert interviews, and concept elicitation (CE) interviews with patients with HF (n = 26) were used to develop a conceptual model of the core symptoms and impacts of HF. To capture these concepts, three new fit-for-purpose PRO questionnaires were constructed in accorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…While many studies have previously found that HF limits physical activity in these patients, the primary focus of these interview studies has been on symptoms. 8,13 This study, however, focused on physical activity and provides an in-depth understanding of the different important aspects to physical limitations experienced by patients to a degree of detail that has not previously been reported. The current study included oneon-one interviews with patients to identify the core mobility impairments that patients experience, how these are related to symptoms, and how they impact broader limitations in day-to-day functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many studies have previously found that HF limits physical activity in these patients, the primary focus of these interview studies has been on symptoms. 8,13 This study, however, focused on physical activity and provides an in-depth understanding of the different important aspects to physical limitations experienced by patients to a degree of detail that has not previously been reported. The current study included oneon-one interviews with patients to identify the core mobility impairments that patients experience, how these are related to symptoms, and how they impact broader limitations in day-to-day functioning.…”
Section: Discussionmentioning
confidence: 99%
“…For example, HF patient interview studies consistently identify dyspnoea, fatigue, and peripheral oedema as key symptoms experienced by patients. 8,13 The studies have also identified broad areas of physical activity, such as walking, climbing stairs, and lifting and carrying items, as relevant for HF patients. However, they were not designed to specifically focus on physical activity limitations and, therefore, do not provide detailed descriptions of the limitations that HF patients face in their day-to-day lives.…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure in the US is expected to affect 8.5 million individuals by 2030, with a high percentage of deaths related to mismanagement of the disease 1. Hospital admission due to CHF symptom exacerbation contributes to the highest frequency of 30-day readmissions.…”
Section: Introductionmentioning
confidence: 99%
“…mismanagement of the disease. 1 Hospital admission due to CHF symptom exacerbation contributes to the highest frequency of 30-day readmissions. This lowers insurance reimbursement rates and requires hospitals to monitor the discharge process to prevent reoccurrence by evaluating the intensity of treatment and assessing the discharge status of those readmitted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation